E-Catalog Produk Untuk Menunjang Presentasi Produk Bank Jateng - Vebyana Kusumawardani; Ina Sholihah Widiati; Febrianta Surya Nugraha (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
The era is increasingly developing, technology is increasingly modern, one of which is a smartphone, with a smartphone activities have been helped for communication, work to style. Android-based smartphones have offered their touch and play applications to become the flagship devices of today's technology. E-catalog is an information system from a catalog that can be accessed digitally. The purpose of creating this system is to support the paperless program launched by the Sukoharjo Branch of Bank Jateng. In making this system, it includes various Bank Jateng products, filling out customer and prospective customer forms, and being able to contact Bank Jateng officers at the Sukoharjo Branch. The design of this application uses Adobe Animate CC 2021 software and the programming language used in designing this E-Catalog system is Action Script 3.0. The results of research at Bank Jateng Sukoharjo Branch, it can be concluded that with this E-Catalog system it can make Marketing and Customer Service easier in marketing and Customers and Prospective Customers can easily understand from this Android-based E-Catalog.